The governance of risk - Crowther, David; Aras, Güler (Emerald, 2013)
The relationship between economic or social or political activity and risk is widely recognised at a societal level, a market level and a business level, and equally widely discussed. The relationship between governance and risk at all of these levels is equally widely recognised but much less widely discussed. But the consequences of poor governance in this arena have been exposed to all in the recent financial and economic crisis as financial institutions and even countries have collapsed or come close to collapsing. The relationship between governance and risk is particularly important in the global environment in which we operate and needs to be more fully discussed and theorised. This book is designed to address important aspects of this topic and set it within the context of the global business and societal environment.
Includes index.
Keywords: Corporate governance.; Social responsibility of business.; elektronické knihy; electronic books